(untitled) (International Conference on Computers in Education, 2023)
The purpose of this study is to construct a companion robot behavior model that provides a learning environment enhancing learners’ motivation to learn by inducing peer awareness. Particularly, inducing "peer-ness" through robot behavior has an impact on education. Therefore, we verified a robot behavior model oriented to induce "peer-ness," including inducing a "sense of competition," through long-term nonverbal interactions. The results of this study confirmed the "peer-ness" induction and demonstrated the validity, although it varied depending on the mental state.